Microwave ablation vs. surgery for T1bN0M0 papillary thyroid carcinoma: a propensity score-matched cohort study - Zhao, Xinshu; Wang, Peiwen; Teng, Deng-Ke (Frontiers in Endocrinology, 2026)
ObjectiveTo assess the efficacy and safety of microwave ablation (MWA) in treating T1bN0M0 (T1b) papillary thyroid carcinoma (PTC) by comparing patient outcomes with those following surgical resection in treating T1b PTC.MethodsIn this retrospective analytical study, patients who were diagnosed with T1b PTC in the ultrasound department of our hospital between April 2019 and October 2023. The patients were divided into MWA group and surgery group according to the different treatment methods. A 1:1 propensity score matching (PSM) analysis was performed to compare local tumor progression (LTP), relapse-free survival (RFS), and complication rates between patients treated with MWA and surgical resection.ResultsAfter 1:1 PSM accounting for sex, age, nodule location, position and follow-up time as potential confounders, 172 patients with T1b disease were matched with 1:1 PSM, 86 patients each in the surgery and MWA treatment groups. Following PSM, there was no statistically significant difference in LTP (2.33% vs. 3.49%, p = 0.650) between the MWA group and the surgical group. The volume reduction rate (VRR) was 98.53 ± 6.50%. No permanent complications were observed after MWA, and no cases of distant metastasis or delayed surgery occurred.ConclusionsMWA could serve as a reasonable alternative besides surgery for T1b patients.